The Incas - Davies, Nigel, 1920-2004. (Niwot, Colo. : University Press of Colorado, 1995)
"Readable summary of the history, imperial infrastructure, mechanisms of control and integration, and other unique characteristics of the Inca Empire"--Handbook of Latin American Studies, v. 57.
In search of the past -- The first of the Incas -- The era of Pachacutec -- The last conquerors -- The Inca state -- The empire and its infrastructure -- The imperial system -- The decline and fall.
Includes bibliographical references (pages 233-247) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Incas -- Politics and government; Incas -- History -- Sources; Incas -- Antiquities; Ethnohistory -- Andes Region; Andes Region -- Antiquities; Incas -- History -- Sources; Incas -- Politique et gouvernement; Incas -- Histoire -- Sources; Incas -- Antiquités.; Ethnohistoire -- Andes; Andes -- Antiquités.; Incas -- Histoire -- Sources; HISTORY; SOCIAL SCIENCE -- General; Antiquities; Ethnohistory; Incas; Incas -- Antiquities; Incas -- Politics and government; Andes Region; Inka's.; Electronic books; History; Sources; Sources